Uma unidade de ensino potencialmente significativa para ensinar fontes de energia - Piffero, Elaine de Lourdes Fontana (2017)
This paper reports a Potentially Significant Teaching Unit (PSTU) on energy sources. The didactic proposal was based on the Ausubel Learning Theory and on the didactic proposal elaborated by Moreira (2011), focusing on Science-Technology-Society (CTS). The research work was developed in a state school in the 9th year of elementary education in the city of Alegrete / RS. The sequence consisted of the eight steps of the PSTU suggested by Moreira (2011). With initial activities for the verification of previous knowledge, pedagogical visits to two thermoelectric power plants in the city and the Campus of Unipampa / Alegrete, several researches on the theme, exhibition of movies, use of scientific texts, construction of scale models and summative evaluations. The content approach has always been exposed in a more general way, moving to a more specific approach to each subject, aiming for progressive differentiation and later integrative reconciliation. It was verified that the teaching unit showed evidences of the learning evolution of the concepts of the majority of the students regarding the contents related to energy sources and their implications and to the relations between Science, Technology and Society, including environmental and political aspects, perceived through of the materials produced, as in oral and written reports and quantitative analysis of summative evaluations. From the results obtained, it was constructed as educational products, a hypertext and a printed booklet, with the stages of the PSTU that can be adapted and implemented in different